[Zdeněk Svoboda 5.]
1946-1967: wedding ceremony, vacation in the Tatra mountains, speed-race, first day in the school, political speech, vacation in a weekend-house, travelling to Bulgaria (across Budapest, Kolozsvar), summer vacation in the Soviet Union, the Crimeria